The rat's sciatic nerve functional index dynamics after its transection and recovery by means of epineural neurorrhaphy - Ziia K. Melikov; Volodymyr V. Medvediev (Ukrainian Neurosurgical Journal)
Introduction. Peripheral nerve injury (PNI) is a common wartime pathology, the presence of which significantly complicates the course and treatment of combat injuries to the limbs. The development of new methods of treatment of PNI is impossible without validating existing models of PNI and clarifying the dynamics of the recovery process in this type of injury over long periods of observation. In this paper, the dynamics of the sciatic functional index (SFI) after transection and immediate suturing of the sciatic nerve of an adult rat during 24 weeks of observation was analyzed in detail. Objective: to analyze the dynamics of SFI after transection, as well as after transection and immediate suturing of the sciatic nerve of an adult rat for 24 weeks and compare the obtained results with the data of other authors under similar experimental conditions. Materials and Methods. The study was performed on 76 white adult outbred male rats, adhering to bioethical norms. In animals of the Sham group (n=24) an access to the sciatic nerve was performed, in animals of the Sect group (n=29) — the sciatic nerve was transected, and Raph group (n=23) — transection and immediate epineural suturing of the sciatic nerve was performed. A certain number of animals were removed from each group 4, 8, and 12 weeks after surgery for electrophysiological and morphological studies, and for the rest of the animals, the experiment was completed 24 weeks after the start of observation. SFI was determined before animals were removed, for all animals in each group at 4, 8, 12, 16, 20 and 24 weeks according to the Bain-Mackinnon-Hunter formula. Processing of digital data was carried out by various means of mathematical statistics. Results. In animals of the Sham group, which were observed throughout the entire 24 weeks of the experiment (n=7), the average value of SFI one month after the injury simulation was -8.9 points and did not change significantly until the end of the experiment. In animals of the Sect group, which were observed throughout the entire 24 weeks of the experiment (n=8), one month after the injury, the mean SFI value was –84.7 points, significantly increasing to –67.0 points at the end of the 16th week, and subsequently significantly decreasing to –96.5 points. In animals of the Raph group, which were observed throughout the entire 24 weeks of the experiment (n=7), the average value of SFI after one month was -64.4 points, and its increase to -45.4 points at the end of week 24 should be considered relatively reliable. Pairwise comparison of the averaged for all animals SFI values in the Sham and Sect, Sham and Raph, and Sect and Raph groups revealed significant differences at 4, 8, 12, 20, and 24 weeks after simulated injury. At 16 weeks post-intervention, the SFI values in the Sect and Raph groups were significantly different from those in the Sham group, but were not different from each other. Conclusions. The method of determining the function of the paretic limb after sciatic nerve injury in rats using SFI has a number of technical limitations, which are the reason for significant variability in experimental results among different research groups. The reliable biphasic SFI dynamics that was discovered after sciatic nerve transection, as well as the insignificant (according to this data) fluctuations in SFI after sciatic nerve transection and neurorrhaphy, require independent verification, pathophysiological interpretation, and should be taken into account when evaluating rehabilitation methods using such an experimental model of peripheral nerve injury.